Prepletene polimerne mreže za površinsko dodelavo usnja - Anžlovar, Alojz (Kovine zlitine tehnologije, 1998)
The possibility of using the performed films of interpenetrating polymer networks (IPN) for leather finishing was investigated. Their applicability was estimated by comparing the mechanical properties of IPN and reference PU films as well as by comparing the properties of the leather samples finished with both types of polymer films.
Keywords: polimeri; polimerne mreže; usnje